Objective Semantic and Syntactic Dependence in Lesya Ukrainka’ Language Creativity (Linguostylistic Studies, 2014)
The article makes a point of common patterns and conditions for functioning predicative and substantive components in the semantic and syntactic sentence structure. It has been identified that the semantic simplicity of a sentence construction constitutes a predicate and all substantive syntaxemes dependent on its semantics. It has been indicated that a predicate is able to form subjective, objective, addressee, instrumental and locative semantic and syntactic dependences in a sentence structure. The main focus of the research is the analysis of objective semantic and syntactic dependence in the function of an objective syntaxeme. It is identical to the one-way dependence of a formal syntactic structure that is represented by an adverbial subordinate part of the sentence. It has been found that according to the lexical expression of a predicative component the objective dependence has the following semantic alternates such as dependence on the action object, dependence on the process object, dependence on the state object, dependence on the object of qualitative state, dependence on the object of state and attitude, dependence on the locative object of action. Key words: Objective semantic and syntactic dependence, predicate, objective, syntaxem, structure of the sentence. References